2020
DOI: 10.3390/nano10091874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3 Dot Patterning on CZTSSe Solar Cell Characteristics

Abstract: In this study, a 5-nm thick Al2O3 layer was patterned onto the Mo electrode in the form of a dot to produce a local rear contact, which looked at the effects of this contact structure on Cu2ZnSn(S1-xSex)4 (CZTSSe) growth and solar cell devices. Mo was partially exposed through open holes having a square dot shape, and the closed-ratios of Al2O3 passivated areas were 56%, 75%, and 84%. The process of synthesizing CZTSSe is the same as that of the previous process showing 12.62% efficiency. When the 5-nm-Al2O3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Recently, Kim's group reported CZTSSe solar cells with the Al 2 O 3 pattern on Mo produced by the photolithography process. [ 156,157 ] They revealed that voids tend to form near the Al 2 O 3 , while the kesterite phase self‐aligned with the pattern‐opening area. This self‐align feature was attributed to the different wettability and bonding between the liquid phase Sn and the metal/metal oxide surface.…”
Section: Back Contact Interface Engineeringmentioning
confidence: 99%
“…Recently, Kim's group reported CZTSSe solar cells with the Al 2 O 3 pattern on Mo produced by the photolithography process. [ 156,157 ] They revealed that voids tend to form near the Al 2 O 3 , while the kesterite phase self‐aligned with the pattern‐opening area. This self‐align feature was attributed to the different wettability and bonding between the liquid phase Sn and the metal/metal oxide surface.…”
Section: Back Contact Interface Engineeringmentioning
confidence: 99%